Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi di Provinsi Sumtera Barat - Sidik Alamin, Rafi (Green Publisher Indonesia, 2025)
Economic growth is a major indicator of a country's progress, which is influenced by factors such as exports, imports, and population. This study aims to analyze the influence of these variables on economic growth in West Sumatra Province in the 2016-2020 period. This research offers a new approach by combining macro and micro factors to analyze GDP, export-import, and population at the regional level. The method used is multiple linear regression with secondary data obtained from the Central Statistics Agency (BPS). The results of the study show that exports have a negative but insignificant effect on economic growth, while imports have a positive influence that is also not significant. On the contrary, the number of people has been proven to have a positive and significant influence on economic growth. These results emphasize the importance of managing population and other economic sectors to support regional competitiveness. This research provides insights for policymakers in designing more effective economic recovery strategies in West Sumatra Province.